Penal Policy: Quo Vadis Pengaturan Persidangan Perkara Pidana Secara Online di Masa Pandemi Covid-19 - Raden Muhammad Arvy Ilyasa; Ahsana Nadiyya; Dede Indraswara (CV Rewang Rencang, 2021)
The Covid-19 pandemic has affected people's lives, including in the aspect of law enforcement related to the implementation of online criminal trials. The implementation of online trials is regulated in the Supreme Court of the Republic of Indonesia Regulation (PERMA) Number 4 of 2020 concerning the Administration and Trial of Criminal Cases at Courts Electronically. The implementation of online trials raises juridical-procedural problems, regarding the umbrella act. The affirmation of the PERMA in the invitation hierarchy still raises problems, so a more established regulation is needed in the form of a regulation in lieu of laws (Perppu) through criminal law policy (Criminal Policy) to realize legal certainty for justice seekers during the Covid-19 pandemic. The method used in this assessment is normative juridical.